2012
DOI: 10.1177/0961203312450085
|View full text |Cite
|
Sign up to set email alerts
|

Serum procalcitonin has negative predictive value for bacterial infection in active systemic lupus erythematosus

Abstract: PCT may be a better marker to rule out bacterial infection in lupus flare but not in remission or general screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
3
19
2
2
Order By: Relevance
“…In contrast to previous data, demonstrating no diagnostic value for bacterial infection in AID patients [ 7 , 8 ], but in line with other reports [ 9 , 10 ], we detected the utility of PCT for differentiating between bacterial infection and nonbacterial condition. The ambiguous conclusions may be attributable to several factors: First, enrolled difference kind of AID or heterogeneous groups of patients as controls.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to previous data, demonstrating no diagnostic value for bacterial infection in AID patients [ 7 , 8 ], but in line with other reports [ 9 , 10 ], we detected the utility of PCT for differentiating between bacterial infection and nonbacterial condition. The ambiguous conclusions may be attributable to several factors: First, enrolled difference kind of AID or heterogeneous groups of patients as controls.…”
Section: Discussionsupporting
confidence: 88%
“…18 Specifically, low serum PCT levels (<0.17 ng/ml) had >90% negative predictive value for ruling out bacterial infection in SLE patients. 19 A review of the literature published until 2014 indicated that raised PCT levels ≥0.5 μg/L should strongly suggest bacterial infection in the context of SLE. 20 However, there is limited data regarding the diagnostic accuracy of PCT in case of hemophagocytic syndrome, a severe condition which can mimic or complicate both lupus flare and infection.…”
mentioning
confidence: 99%
“…Whether PCT can serve as an indicator to distinguish the two statuses in SLE remains controversial. [12][13][14] Sfia et al 15 reported that in eight cases with severe drug eruption, one case of SJS and one case of drug rash with eosinophilia and systemic symptoms in the absence of bacterial infections had significantly elevated PCT levels. In such cases, PCT may not be a reliable marker to discriminate between infection and no infection.…”
Section: Discussionmentioning
confidence: 99%